Hubungan Antara Self-Compassion dan Self-Efficacy dengan Social Anxiety Siswa SMA Negeri Suku Banjar - Heiriyah, Ainun; Sanjaya, Sanjaya; Futri, Elisa; Awalia, Awalia (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2024)
The research findings indicate a significant positive correlation between self-compassion and social anxiety among Banjar State High School students, with a correlation coefficient of r = 0.396 and a p-value of 0.000, which is less than 0.05. Additionally, there is a significant positive correlation between self-efficacy and social anxiety, with a correlation coefficient of r = 0.364 and a p-value of 0.000 (p < 0.05). When examined together, self-compassion and self-efficacy show a significant combined relationship with social anxiety, yielding a correlation coefficient of r = 0.434 and a p-value of 0.000 (p < 0.05). This combined effect is stronger than the individual correlations of self-compassion (r = 0.396) and self-efficacy (r = 0.364) with social anxiety. Thus, the hypothesis stating that there is no relationship between self-compassion, self-efficacy, and social anxiety among Banjar State High School students is rejected.